Table of Content - -, (Journal of Educational and Psychological Sciences, 2025)
:Table of Content• Determinants Associated with School Discipline in Schools of Tuwaiq Educational Office (Riyadh) for the Year 2025: A Descriptive-Analytical Study of Students' PerceptionsMr. Dhafer S. Al-Shehri , Dr. Manal A. Al-Qayawi ,Mr. Hassan H. Musawi , Dr. Amaal S. Al-Uraini , Dr. Modi S. Al-Uraini• The degree of use of quality standards in programs provided for students with learning difficulties in the First Zarqa Education Directorate from the point of view of teachersMr. Marwan Qassem Ebrahem Bany Issmail• The role of Saudi universities in facing some contemporary challenges from the point of view  of faculty members in colleges of educationDr. Alya Ali Aloqayli• The Impact of Studying Prophetic Hadiths on the Educational Behavior of Ninth-Grade Female Students in the State of KuwaitMs. Nora Faleh Al-Ajami• An Analytical Survey Study of Arabic Research Dealing with the Guidance of Gifted Students  from 2018-2023Ms. Zainab Abdullah Al Safar, Co-Prof. Abdul-Hamid Abdullah Al-Arfaj• Suggestibility and its Relationship to Psychological Needs among Sample of Drug Addicts  in the Irada Complex in JeddahMs. Samia Ahmed Al-Ghamdi, Dr. Muhammad Jafar Jamal Al-Layl• Personal traits of women and their educational applicationsMr. Hamzeh Mohammad Mandahawi
Keywords: Journal of Educational and Psychological Sciences